Genomics and Mapping of Teleostei (Bony Fish). Issue 2 (2003) - Clark, Melody S.
Abstract : Until recently, the Human Genome Project held centre stage in the press releases concerning sequencing programmes. However, in October 2001, it was announced that the Japanese puffer fish ( Takifugu rubripes, Fugu ) was the second vertebrate organism to be sequenced to draft quality. Briefly, the spotlight was on fish genomes. There are currently two other fish species undergoing intensive sequencing, the green spotted puffer fish ( Tetraodon nigroviridis ) and the zebrafish ( Danio rerio ). But this trio are, in many ways, atypical representations of the current state of fish genomic research. The aim of this brief review is to demonstrate the complexity of fish as a group of vertebrates and to publicize the 'lesser-known' species, all of which have something to offer.